Arduino + Android projects for the evil genius : control Arduino with your smartphone or tablet - Monk, Simon (McGraw-Hill's AccessEngineering., 2012)
Featuring two hot technologies, this book shows electronic hobbyists and experimenters how to create cool Arduino devices and use their Android smartphones and tablets to monitor and control them!.